Creencias colectivas en la escuela pública - Córdova, Elizabeth Rosales (2009)
This article presents the qualitative analysis of public teachers’ interviews who worked at low socioeconomic schools. We found that school contexts condition teachers’ beliefs about students’ performance and achievement. Through the emphasis on students’ difficulties, teachers reduce their responsibility for student learning. However, institutional activities oriented to teachers’ change may be related to strengthen collective efficacy beliefs which diminish their beliefs about negative conditions of low socioeconomic contexts, and motivate teachers’ pedagogical change.